ANALISIS PENURUNAN SUSUT NON-TEKNIS DENGAN METODE ANALISA LOAD PROFILE BERBASIS AMR PADA PELANGGAN POTENSIAL PT. PLN (PERSERO) ULP TALIWANG: ANALISIS PENURUNAN SUSUT NON-TEKNIS DENGAN METODE ANALISA LOAD PROFILE BERBASIS AMR PADA PELANGGAN POTENSIAL PT. PLN (PERSERO) ULP TALIWANG - BUDI PRAMONO JATI; ARDIANSYAH DWI ADHA ISKANDAR (UNIVERSITAS PGRI MADIUN, 2026)
budipramono@unissula.ac.id ABSTRACT Non-technical losses in electricity distribution pose a significant challenge to the operational efficiency and revenue of PT. PLN (Persero). This study aims to analyze the reduction of non-technical losses through the application of Automatic Meter Reading (AMR) technology, focusing on the load profile analysis of potential customers at PT. PLN ULP Taliwang. The research method includes field observation, energy consumption data collection via AMR, and customer consumption pattern analysis. The results indicate that AMR effectively detects consumption anomalies such as electricity theft and recording errors, significantly reducing non-technical losses by 50% to 80%. This technology also contributes to improved grid efficiency, operational cost savings, and increased company revenue. The study recommends broader implementation of AMR and customer education as optimal strategies to address non-technical losses. Keywords: Non-Technical Losses, AMR, Load Profile, PLN, Energy Efficiency